Effect of Neutral Grounding Protection Methods for Compensated Wind/PV Grid-Connected Hybrid Power Systems - Nurettin Çetinkaya; Farhana Umer (International Journal of Photoenergy)
The effects of the wind/PV grid-connected system (GCS) can be categorized as technical, environmental, and economic impacts. It has a vital impact for improving the voltage in the power systems; however, it has some negative effects such as interfacing and fault clearing. This paper discusses different grounding methods for fault protection of High-voltage (HV) power systems. Influences of these grounding methods for various fault characteristics on wind/PV GCSs are discussed. Simulation models are implemented in the Alternative Transient Program (ATP) version of the Electromagnetic Transient Program (EMTP). The models allow for different fault factors and grounding methods. Results are obtained to evaluate the impact of each grounding method on the 3-phase short-circuit fault (SCF), double-line-to-ground (DLG) fault, and single-line-to-ground (SLG) fault features. Solid, resistance, and Petersen coil grounding are compared for different faults on wind/PV GCSs. Transient overcurrent and overvoltage waveforms are used to describe the fault case. This paper is intended as a guide to engineers in selecting adequate grounding and ground fault protection schemes for HV, for evaluating existing wind/PV GCSs to minimize the damage of the system components from faults. This research presents the contribution of wind/PV generators and their comparison with the conventional system alone.